Biofortified maize - International Food Policy Research Institute (International Food Policy Research Institute, 2006)
Maize is the preferred staple food of more than 1.2 billion people in Sub-Saharan Africa and Latin America. Over 50 million people in these regions are vitamin A deficient. Maize-based diets, particularly those of extremely poor individuals, often lack essential vitamins such as vitamin A. Dietary sources occur either as preformed vitamin A, as in dairy and other foods from animal sources, or as provitamins A, as found in plant foods, including maize. Identifying and increasing the supply of maize cultivars rich in provitamins A may greatly improve the health and longevity of people around the world.